Energy-efficient shaping of contemporary buildings and their surroundings as an essential element of modernization of built-up areas = Energooszczędne kształtowanie współczesnej zabudowy i jej otoczenia, jako niezbędny element modernizacji obszarów zabudowy - Bocheński, Stanisław; Bocheńska-Skałecka, Anna; Kuczyński, Tadeusz (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
A comprehensive design of a building along with the development of a surrounding land may counterbalance the tendency of housing estates comprising houses built on the basis of "ready-made projects" - which have no references to the existing urban tissue and which do not create a new one. In the first place, the energy intensity of buildings using the so-called passive methods should be lowered, and only then active systems should be applied, considering economic balance. The problem should be considered from two different perspectives i.e. for intensively and for less urbanised areas. The article results in the formulation of guidelines for energy-efficient modernization of contemporary buildings and their surroundings.
Keywords: architektura energooszczędna; współczesna zabudowa; modernizacja współczesnej zabudowy; systemy pasywne; systemy aktywne; energy-efficient architecture; modernization of contemporary buildings; contemporary buildings; passive systems; active systems